Memory and Enculturation - Bihari Nagy, Éva (Ethnographica et Folkloristica Carpathica, 2024)
It may be safely stated at present that the triad of past, tradition and memory has accelerated at an incredible pace. Memory seems to keep the events of the past alive for ever shorter periods of time. Rites, memories and remembrance are now handed down as written sources in the form of textbooks. How does the narrative of the teaching aids that have emerged in the 21st century then evolve and what are/have been their achievements in the construction of national identity? How do hon- és népismeret [Our homeland and its people] textbooks function as tools for building a national community? The subject hon- és népismeret taught in grade schools examines and discusses national culture and the processes of cultural reconstruction in a rather specific cross-section. Beyond exploring the interdependence and interlocking of the context and practice of ‘knowledge creation’/‘knowledge transmission’ in primary educational institutions, this paper aims to explore some salient observations on its generational relationship to memory. The importance of this subject and textbook is/has been undeniable, both as a tool for national and social community-building on the one hand and as a tangible archive of the process of heritage transmission/patrimonization on the other hand.